Global Research Trends in Urban Waterfront Redevelopment and Quality of Life: A Bibliometric Analysis (2000–2025) - Altwaijri, Ahmad K.; Alhammad, Bader A.; Alhowaish, Abdulkarim K. (Journal of Cultural Analysis and Social Change, 2026)
This paper presents a bibliometric and thematic analysis of global research on urban waterfront redevelopment and its relationship with quality of life (QoL) published between 2000 and 2025. Using publications indexed in Scopus and Web of Science, the study employs VOSviewer to examine publication trends, intellectual structures, thematic clusters, and patterns of international collaboration. The results reveal a clear conceptual shift from real estate-driven redevelopment toward broader socio-ecological priorities, including sustainability, climate resilience, blue-green infrastructure, and public health. Rather than empirically validating impacts, the literature increasingly frames waterfronts as strategic spaces for enhancing urban livability. Four dominant thematic clusters are identified: (1) sustainable planning and climate adaptation; (2) ecosystem services and environmental restoration; (3) quality of life and livability; and (4) governance, participation, and place attachment. Despite the growing body of research, significant gaps remain, particularly in fast-growing coastal cities, where empirical evidence is limited. Regional disparities are also evident: China, the United States, and European countries dominate academic production, while cities in the Gulf and Middle East remain underrepresented despite substantial waterfront investments. The findings highlight the need for broader multilingual data sources, increased use of empirical and mixed-methods research, and stronger regional and international collaboration to advance both theoretical and practical knowledge. Overall, the analysis positions waterfront redevelopment as a key component of contemporary urban livability discourse, while cautioning against assumptions of empirically confirmed effects on QoL.